Pengembangan Media Pembelajaran Video Animasi Untuk Materi Aku Suka Bergotong Royong di Kelas I Sekolah Dasar - Armita, Finna; Ain, Siti Quratul (Cetta: Jurnal Ilmu Pendidikan, 2025)
The purpose of this research is to develop animated video learning media for the subject of Civic Education material “I Like Mutual Cooperation” for grade I elementary school students. This media is designed to increase students' interest and strengthen their understanding of the material. This development research uses the ADDIE (Analysis, Design, Development) model with stages including material analysis, media product design, and development which includes validation testing. The research subjects involved two material experts, two media experts, and two linguists as validators. The validation results showed that the animated video was highly valid with an accuracy rate of 95% from the media expert, 86.25% from the material expert, and 85% from the linguist. Overall, the average validation from the three experts reached 88.75% with very valid criteria. This finding contributes significantly to the provision of innovative and relevant learning resources for thematic learning in grade I, especially in facilitating the understanding of the concept of gotong royong in a more interesting and effective way.